GAME MEDIA DEVELOPMENT CROSS PUZZLES IN LEARNING SUMMARY EXPLANATION TEXT - Yunita Lestari; Nugraheti Sismulyasih Sb (Education Generation Journal, 2022)
This research is based on Indonesian language learning that has not been effective yet, the result of learned is not optimal yet, to overcome this problem, the researcher developed crossword puzzle game. This development research aims to produce crossword puzzle products as well as know the feasibility and effectiveness of the product. The subjects of this study are the students of class V which amounted to 34 students. Data analysis techniques used to descriptive percentage and n-gain test. The results showed that the media of crossword puzzles is very feasible to use with the percentage of assessment 89.58%, material expert judgments of 88, 63%. The result of N-gain analysis showed that the value obtained is 0.5226 in the medium category and the response is very good. The conclusions of this research is the crossword puzzle game to summarize the developed explanation text is declared eligible and effective in improving the writing skill of the students' explanatory text.